Modeling the Effect of Potential Nitric Acid Removal During Convective Injection of Water Vapor Over the Central United States on the Chemical Composition of the Lower Stratosphere. Issue 16 (23rd August 2019) - Clapp, C. E.; Anderson, J. G.
Abstract: Tropopause‐penetrating convection is a frequent seasonal feature of the Central United States climate. This convection presents the potential for consistent transport of water vapor into the upper troposphere and lower stratosphere (UTLS) through the lofting of ice, which then sublimates. Water vapor enhancements associated with convective ice lofting have been observed in both in situ and satellite measurements. These water vapor enhancements can increase the probability of sulfate aerosol‐catalyzed heterogeneous reactions that convert reservoir chlorine (HCl and ClONO2 ) to free radical chlorine (Cl and ClO) that leads to catalytic ozone loss. In addition to water vapor transport, lofted ice may also scavenge nitric acid and further impact the chlorine activation chemistry of the UTLS. We present a photochemical model that resolves the vertical chemical structure of the UTLS to explore the effect of water vapor enhancements and potential additional nitric acid removal. The model is used to define the response of stratospheric column ozone to the range of convective water vapor transported and the temperature variability of the lower stratosphere currently observed over the Central United States in conjunction with potential nitric acid removal and to scenarios of elevated sulfate aerosol surface area density representative of possible future volcanic eruptions or solar radiation management. We find that the effect of HNO3 removal is dependent on the magnitude of nitric acid removal and has the greatest potential to increase chlorine activation and ozone loss under UTLS conditions that weakly favor the chlorine activation heterogeneous reactions by reducing NOx sources. Plain Language Summary: Some summertime storms in the Central United States are strong enough to transport water uniquely deep into the atmosphere and up into the normally very dry stratosphere, which houses the ozone layer. Moistening the stratosphere changes its chemical balance. The additional moisture results in the transformation of normally inert halogen compounds, including chlorine and bromine, into chemically highly reactive forms that destroy ozone. This activation of inert halogen compounds and ozone loss is dependent on the amount of water added to the stratosphere and the temperature of the stratosphere. Not every storm that transports water into the stratosphere will result in halogen activation and ozone loss, only those that transport significant amounts of water and/or those that overlap with the coldest parts of the stratosphere. The influence of storms on the chemistry of the stratosphere, however, may not be limited to only water. Nitric acid, which plays a role in slowing the activation of inert halogen compounds, may also be removed. We simulate the chemical effects of a range of potential nitric acid removal in conjunction with moistening of the stratosphere. We find that nitric acid removal has the potential to most exacerbate halogen compound activation and ozone loss when the moistening would normally only have mild effects on the stratosphere. Should nitric acid removal be a common occurrence during these stratosphere‐moistening storms, the fraction of storms that can lead to halogen activation and ozone loss is larger than previously thought. Key Points: Photochemical box model defines the vertically resolved response of the stratosphere chemical composition to convective perturbation Effect of nitric acid removal on column ozone loss is dependent on favorability of initial conditions to heterogeneous chlorine activation Nitric acid removal has the most impact on column ozone loss under conditions of mild favorability to chlorine activation